Cellular Distribution of NMDA Glutamate Receptor Subunit mRNAs in the Human Cerebellum - Clemens R. Scherzer; G.Bernhard Landwehrmeyer; Julie A. Kerner; David G. Standaert; Zane R. Hollingsworth; Lorrie P. Daggett; Gönül Veliçelebi; John B. Penney, Jr.; Anne B. Young (Neurobiology of Disease, 1997)
We have used a quantitativein situhybridization method with human ribonucleotide probes to examine the regional and cellular distribution ofN-methyl-d-aspartate receptor (NMDAR) subunit mRNAs in the human cerebellum. Purkinje cells showed very dense labeling for NMDAR1 mRNA, dense labeling for NMDAR2A mRNA, and moderate labeling for NMDAR2D mRNA, whereas labeling for NMDAR2C mRNA was low. Granule cells showed high hybridization signals for the NMDAR1 and NMDAR2C mRNAs and moderate signals for the NMDAR2A and NMDAR2D mRNAs. In addition intense labeling with the NMDAR2B probe was observed in medium-sized neurons with chromophilic cell bodies in the upper part of the granule cell layer, most likely representing Golgi cells. Neurons in the molecular layer, i.e., basket cells and stellate cells, showed moderate hybridization signals for NMDAR1 and NMDAR2D and low signal for NMDAR2C. Each type of cerebellar neuron analyzed displayed a distinct NMDAR2 subunit profile, suggesting that they are likely to have NMDA receptors with distinct properties.